Clinical characteristic of myelin oligodendrocyte glycoprotein antibody associated cortical encephalitis in adults and outcomes following glucocorticoid therapy - Yuqing Wu; Hao Zhou; Xiaojiao Ci; Liuyu Lin; Da Zhang; Jie Lu (Frontiers in Aging Neuroscience, 2023)
ObjectiveTo describe the clinical and radiological features, as well as outcomes following glucocorticoid therapy and recurrence in adults suffering from cortical encephalitis associated with myelin oligodendrocyte glycoprotein (MOG) antibody.MethodsThe clinical information of nine adult patients suffering from cortical encephalitis associated with MOG antibody admitted to the Affiliated Brain Hospital of Nanjing Medical University from 2020 to 2022 was systematically reviewed. The clinical symptoms, laboratory data, imaging results, outcomes following glucocorticoid therapy and recurrence were evaluated.ResultA total of 9 patients positive for MOG antibody and suffering from cortical encephalitis were included in our study (55.6% men, median age 29 years, 15–57 years). The most common clinical symptoms included headache (77.8%), fever (66.7%), and generalized seizures (55.6%). Some patients also experienced limb shaking (22.2%), leg numbness (22.2%), transient motor aphasia (11.1%), and vision loss (11.1%). The main features of cerebrospinal fluid () examination were increased intracranial pressure, pleocytosis, and elevated cerebrospinal fluid (CSF) protein. In addition, N-methyl-D-aspartate receptor (NMDAR) and MOG antibodies were found in the CSF of 3 patients, and NMDAR, MOG, and glial fibrillary acidic protein antibodies were found in the CSF of 1 patient. All patients were subjected to magnetic resonance imaging (MRI) and the images of eight of them showed T2 and/flair image hyperintense lesions, three showed meningeal or lesion enhancement and four showed white matter lesions, which were mostly located in the midline structures (75%). All patients received glucocorticoid therapy in the acute phase and in remission, and eight of them received an intravenous high dose of methylprednisolone, including one patient who received a simultaneous immunoglobulin therapy. One patient was treated with low-dose prednisolone tablets. Seven (77.8%) patients were wholly recovered at discharge, and 2 (22.2%) patients were left with slight symptoms. During the median 9-month follow-up (range: 2–36 months), 2 (22.2%) patients developed recurrence.ConclusionThe clinical manifestations of adult MOG antibody-associated cortical encephalitis were significantly different from those of the typical MOG antibody-associated disease (MOGAD). Patients in the acute phase of the disease were prone to show signs similar to central nervous system infection, requiring clinicians to have the ability to recognize the disease to avoid misdiagnosis. In addition, seizures were common in MOG antibody-related encephalitis, and the type of seizures was age-related. Brain MRI results showed that the distribution of cerebral cortex lesions was closely related to the classification of cortical encephalitis. Based on the patient’s response to the treatment, glucocorticoid therapy was effective against MOG antibody-associated cortical encephalitis, which is consistent with the treatment response and clinical prognosis of MOGAD. Therefore, our opinion was that MOG antibody might be the “responsible antibody” in MOG antibody-associated cortical encephalitis, although further studies are needed to confirm this hypothesis.